2006
DOI: 10.1515/hf.2006.108
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of natural durability of commercial available European and Siberian larch by near-infrared spectroscopy

Abstract: The natural durability of larch wood is described as being highly variable, ranging from non-durable to durable. In this study, FT-NIR spectroscopy was investigated for its ability to predict the natural durability of commercially available larch wood. Samples originated from approximately 60 European and 25 Siberian larch trees, provided by three Austrian-based wood industries. Natural durability tests were performed using the test fungi Gloeophyllum trabeum and Coniophora puteana. FT-NIR spectra were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Wood is a remarkably naturally durable material. This natural durability in terms of decay resistance against fungi, varies in a wide range between species and even within species [78][79][80] and can also be predicted by infrared spectroscopy [78,81,82]. The natural durability of wood mainly depends on the extractives composition [79,83] but also on the extractives content [79] and is in general higher in hardwoods than in softwoods.…”
Section: Natural Durability Of Wood -Preventing Wood From Degradationmentioning
confidence: 98%
“…Wood is a remarkably naturally durable material. This natural durability in terms of decay resistance against fungi, varies in a wide range between species and even within species [78][79][80] and can also be predicted by infrared spectroscopy [78,81,82]. The natural durability of wood mainly depends on the extractives composition [79,83] but also on the extractives content [79] and is in general higher in hardwoods than in softwoods.…”
Section: Natural Durability Of Wood -Preventing Wood From Degradationmentioning
confidence: 98%
“…Gierlinger et al 2004a;Kokutse et al 2006;Amusant et al 2008) and wood near-infrared (NIR) spectra (e.g. Gierlinger et al 2003;Sykacek et al 2006;Leinonen et al 2008;Bush et al 2011) have been studied in relation to natural durability and proposed as indirect predictors with more or less success.…”
Section: Introductionmentioning
confidence: 99%
“…Various investigations have used NIRS for prediction of such wood properties as stiffness, density and fibre length (Hauksson et al 2001;Schimleck et al 2003;André et al 2006). Predicting wood decay by using NIR was reported by Stirling et al (2007) and Fackler et al (2007), and prediction of natural durability was reported by Sykacek et al 2006. A new review of NIRS research involving wood and paper has been done by Tsuchikawa (2007).…”
Section: Introductionmentioning
confidence: 99%